Efficient deprotection of Boc group in amines and sulfamides using Dawson heteropolyacid catalyst - Belghiche, Roubila; Cheraiet, Zinelaabidine; Berredjem, Malika; Abbessi, Mostefa; Aouf, Nour-Eddine (European Journal of Chemistry, 2012)
A series of sulfamides containing two protecting groups have been synthesized starting from N-benzoylaminoacids derivatives of (glycine, alanine, valine, leucine, phenylalanine), chlorosulfonylisocyanate and primary amines. Selective deprotection of the cyclic or linear sulfamides and amines has been achieved by treatment with heteropolyacid, which is easily recoverable and reusable. This method represents a reasonable alternative to the previous reported deprotection procedures.